Implementation of Legal Protection of Workers with Employment Agreement For A Specified Period of Time (PKWT) Changed Into Employment Agreement for Unspecified Period Of Time (PKWTT) For The Same Job - Deden Achmad Chaerudin; Aloysius Uwiyono (Department of Public Administration, 2023)
Entrepreneurs who employ workers for permanent jobs with an Employment agreement for a Specified Period of Time (hereinafter referred to as “PKWT”) employment relationship that is changed to an Employment agreement for Unspecified Period of Time (hereinafter referred to as “PKWTT”) for the same job after the end of the PKWT employment relationship are mostly carried out in employment practices. Employers do this because the probationary period of 3 months for work relations with PKWTT is felt to be insufficient to assess worker performance in accordance with the targets set by employers. The PKWT is as if it is being used as a probationary period by the employer and the PKWT is not registered by the entrepreneur at the agency that administers government affairs in the district/city manpower sector which will have legal consequences for legal certainty and protection for workers. The government's weak oversight of labor practices in companies has made this kind of PKWT implementation continue and will continue to occur.